Emprego de duas novas cepas de levedura nacional na produção de cerveja artesanal tipo Ale - Januario, Augusto César (2019)
The identification of new efficient yeast is really important, especially for the microbreweries, since 99% of the yeasts used in Brazil are foreign. We have studied the kinetic yeast strains behavior, which are new kinds of Sacharomyces Cerevisiae, an Ale type (high fermentation), during the beer’s fermentation process, we saw a high-quality pattern through the physicochemical and sensory analyses. We made plenty of thirty liters of different kinds of beer to check in which one the yeast has a better fermentation and a better taste. The production followed the steps predicted in the book How to brew and it was made in the kitchen branded Mecbeir, with temperature and brazing control and an automatic pump for the must recirculation. The must was divided in tree brewers, ten liters each, and it was inoculated a commercial yeast in one of them while the new ones were used in the other – three brewers each – to verify the fermentation’s reproducibility. It was determined the fermentative kinetic through the amount of sugar in the must and we found, comparing the different types of yeasts, that the new ones have a good power fermentation and that the process happens in a short time-period – between seven and twelve days. By the end, happened physicochemical analyses following the methodology from the American Society of Brewing Chemists (ASBC) proving the beer’s quality and showing it was inside the patterns demanded from MAPA. In the analysis, it was seen the aroma, taste, foaming, appearance and overall impression through the structured hedonic scale of nine points, demonstrating that beer produced pleased volunteers.